Mortality in Non-COVID-19 Intensive Care Unit During the Pandemic - Özgür Kömürcü; Müzeyyen Beldağlı; Fatma Ülger (Galenos Yayinevi, 2022)
Objective:The coronavirus disease-2019 (COVID-19) pandemic has had a negative impact on all healthcare services. We investigated how the intensive care mortality rate, an important quality indicator of intensive care units, was affected during the pandemic at our center.Materials and Methods:In a retrospective single-center internal surgery setting with a 20-bed intensive care unit, patients without COVID-19 were admitted. The mortality rates over a 6-month time period pre- and postpandemic were compared.Results:During the pandemic, the mortality rate at our intensive care unit has increased. We also observed that there was a significant relationship between mortality and the indication for admission to the intensive care unit (postsurgical admission, postadmission for medical reasons, and post-traumatic) and the place of admission to the intensive care unit (emergency department, different hospital) (p<0.05).Conclusion:During the pandemic period, disruptions in routine health services can cause significant health problems in patients who do not have COVID-19 infection.